Cross-Cultural Usability Testing: Defining Cultural Differences in Product Usage and User Needs Between Dutch and Indonesian Users - Hariandja, Johanna; Daams, Brechtje (Faculty of Psychology, Universitas Surabaya, 2005)
In today's global economy, many products designed by European companies are sold worldwide. These products are used by different user groups in the world with different cultures who think and behave indifferent ways. Cross-cultural usability testing provides the key in defining the cultural differences in product usage and user needs between user groups. In this research, a cross-cultural usability testing of a European product is conducted between Dutch and Indonesian user groups by means of observation and interview. The participants are observed individually on how they use the product, what problems they experienced in using the product and their behavior in using the product and solving the problems they encountered. The usability testing is carried out using the think-aloud' method during the observation, which means that the participants are asked to speak about what they are doing and thinking when using the product. Comparing the results found, it can be concluded that Dutch and Indonesians use and perceive a product in a different way. The findings suggest that cross-cultural usability testing may be very useful when designing products for users with different cultures. It provides a competitive advantage for the companies when entering an international market to ensure equally usable products in different cultures. Dalam era ekonomi global, banyak produk yang dirancang oleh perusahaan Eropa dijual di seluruh dunia. Produk-produk tersebut dipakai oleh kelompok-kelompok penggunayang berbeda dengan budaya yang berbeda yang berpikir dan berperilaku berbeda pula. Uji-gunalintas-budaya merupakan kunci dalam menentukan perbedaan dalam penggunaan suatu produk dan kebutuhan pengguna di antara kelompok- kelompok pengguna. Dalam penelitian ini, suatu uji-gunalintas budaya dari sebuah produk Eropa dilakukan antara kelompok Belanda dan kelompok Indonesia dengan cara observasi dan wawancara. Para partisipan di observasi secara individual bagaimana mereka menggunakan produktersebut, dan bagaimana memecahkan masalah yang dihadapi. Uji guna ini dilakukan dengan metode “think-aloud” selama observasi, yang berarti bahwa para partisipan diminta untuk mengatakan apa yang dilakukan dan dipikirkan ketika menggunakan produk tersebut. Dengan membandingkan hasil-hasil yang diperoleh, dapat disimpulkan bahwa orang Belanda dan orang Indonesia mempersepsi sebuah produk dengan carayang berbeda. Temuan-temuan menyiratkan bahwa uji-guna lintas budaya dapat amat bermanfaat bila merancang produk-produk untuk pengguna dengan berbagai budaya. Ini memberi manfaat kompetitif untuk perusahaan-perusahaan yang memasuki pasar internasional untuk menghasilkan produk-produk yang dapat dipakai sesuai budaya setempat.